Chinese Investment in Latin America: A Case Study of Argentina, and Venezuela - Hira Bashir; Durr e Shahwar Khan; Asia Karim (Journal of Research in Social Sciences)
This article examines the growing influence of Chinese investments in Latin America, focusing on Venezuela and Argentina. It explores how these countries benefit from Chinese capital and how this investment impacts their economies. Venezuela has relied on oil-backed loans to sustain its political system, worsening its economic challenges. In contrast, Argentina has channeled Chinese investment into infrastructure, including hydroelectric dams, nuclear plants, railway modernization, and energy diversification projects. The study highlights that while infrastructure investment can enhance economic stability and reduce reliance on further loans, both countries remain vulnerable due to their dependence on raw material exports. Despite these challenges, the study underscores that with institutional improvements and a shift toward diversification, such investments can contribute to sustainable growth in both nations. A qualitative research approach using secondary sources was employed to analyze the long-term implications of Chinese investments in these two economies.